1996
DOI: 10.1159/000159157
|View full text |Cite
|
Sign up to set email alerts
|

Photorelaxation Is Not Attenuated by Inhibition of the Nitric Oxide-cGMP Pathway

Abstract: Photorelaxation of arteries by ultraviolet (UV) light is hypothesized to result from nitric oxide (NO) released from photoactivable stores. Recently, a study reported enhanced photorelaxation of aortic tissue from rats administered the NO synthase (NOS) inhibitor Nω-nitro-L-arginine (L-NNA). Presumably, the potentiated photorelaxation was due to NO generated from UV-light-induced decomposition of the NO2 moiety of L-NNA. However, we hypothesized that photorelaxation is: (1) not the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Once released, NO targets the haem moiety of soluble guanylate cyclase (sGC) in vascular smooth muscle cells, and thus, activates sGC, leading to an increase in cGMP which acts as a second messenger in a cascade of phosphorylation events resulting in vasodilation. It has been reported that ODQ and methylene blue, inhibitors of sGC, reduce photorelaxation (Charpie et al ., 1994; Furchgott et al ., 1985; Lovren & Triggle, 1998), have no effect (Goud et al ., 1996) or even potentiate photorelaxation (Chen & Gillis, 1993). Furthermore, it has been shown that photorelaxation increases cGMP levels in rabbit and rat aortae through the activation of sGC (Karlsson et al ., 1984; Furchgott et al ., 1985; Chen & Gillis, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Once released, NO targets the haem moiety of soluble guanylate cyclase (sGC) in vascular smooth muscle cells, and thus, activates sGC, leading to an increase in cGMP which acts as a second messenger in a cascade of phosphorylation events resulting in vasodilation. It has been reported that ODQ and methylene blue, inhibitors of sGC, reduce photorelaxation (Charpie et al ., 1994; Furchgott et al ., 1985; Lovren & Triggle, 1998), have no effect (Goud et al ., 1996) or even potentiate photorelaxation (Chen & Gillis, 1993). Furthermore, it has been shown that photorelaxation increases cGMP levels in rabbit and rat aortae through the activation of sGC (Karlsson et al ., 1984; Furchgott et al ., 1985; Chen & Gillis, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…chemical structure of these NOS inhibitors, resulting in NO release. Goud et al [13] refute the NO 2 group hypothesis by observing an enhancement of photorelaxation in the presence of NOS inhibitors which have no NO 2 group. However, our results support the NO 2 group hypothesis.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the NO may be exogenously generated by a photochemical reaction rather than by endogenous NOS in the endothelium. Goud et al [13] suggested that photorelaxation is not attenuated by inhibition of the NO-cGMP pathway, and refuted the NO hypothesis. However, it is possible that their dose of MB (10 6 mol/l) was insu$cient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathway of this mechanism is still not completely solved, but there is evidence of involvement of so-called nitrosothiols. Whereas for a long time nitric oxide was thought to be the active compound in photorelaxation (31), various recent studies have pointed out that S-nitrosothiols account for the relaxation in vascular smooth muscle cells (32)(33)(34)(35), both by nitric oxide release and by direct binding to nitrosothiol recognition sites (33). This is an attractive hypothesis for the increase of skin blood flow in infants receiving phototherapy, as nitrosothiol isomers can suppress baroreceptor reflexes in the aortic arch (33).…”
Section: Subjectsmentioning
confidence: 99%